Evaluasi Program Padat Karya Tunai Desa di Desa Gayam Kecamatan Gayam Kabupaten Bojonegoro - Priyono, Priyono; Hidayat, Kliwon; Asmara, Rosihan (Universitas Musamus, Merauke, Papua, 2024)
This research aims to analyze the issues arising from the Cash for Work Village Program, researchers conducted a study to benefit stakeholders. This research utilizes a Mixed Methods approach by combining both quantitative and qualitative methods. The research employs purposive sampling, a technique that involves selecting research subjects based on specific criteria, not randomly, with the aim of obtaining samples relevant to the research objectives. Data collection techniques include questionnaires, interviews, observations, and documentation. The implementation of the Village Cash For Work Village Program in this study goes through several stages, namely the Planning Stage, which is the most important stage in the implementation of the PKTD Program in Gayam Village. This involves the preparation of the Village Government Work Plan (RKP), which itself goes through several stages: 1) Village Meeting for Development Planning (PPD) Team Meeting for Planning, 2) Measurement of Construction Sites, and Preparation of the Budget Plan for all Activities 3) Development Planning Meeting (Musrenbang) 4) Village Meeting for the Establishment of the Village Government Work Plan. Subsequently, the implementation stage takes place in April and May. Involvement of poor and marginalized families: based on the participation of heads of households and family members, 30 respondents participated, representing 42.85%, while 40 respondents did not participate in the program, representing 57.15%.